Optical waveguide filter design - Thahira, Nabisathul. (2008)
This project aims at designing waveguide filters that can be used effectively in WDM communication systems. These filters provide an efficient means for the effective utilization of the available bandwidth. Also, the extensive applications of these waveguide filters in WDM Systems are studied.